#### Answer

m=-4

#### Work Step by Step

Simplifying
5m + -1(2m + -7) = -5
Reorder the terms:
5m + -1(-7 + 2m) = -5
5m + (-7 * -1 + 2m * -1) = -5
5m + (7 + -2m) = -5
Reorder the terms:
7 + 5m + -2m = -5
Combine like terms: 5m + -2m = 3m
7 + 3m = -5
Solving
7 + 3m = -5
Solving for variable 'm'.
Move all terms containing m to the left, all other terms to the right.
Add '-7' to each side of the equation.
7 + -7 + 3m = -5 + -7
Combine like terms: 7 + -7 = 0
0 + 3m = -5 + -7
3m = -5 + -7
Combine like terms: -5 + -7 = -12
3m = -12
Divide each side by '3'.
m = -4
Simplifying
m = -4